COLLEMBOLA PERMUKAAN TANAH PADA LAHAN SAYURAN CRUCIFERAE DIDESA SERANG, KABUPATEN PURBALINGGA - Ambarningrum, T.B.; Minarni, E.W.; Pratiknyo, H.; , Darsono (Prosiding, 2012)
Collembola are one of the ecosystem components that are important in keeping the ecosystem stability. Beside its role as the decomposer, Collembola also takes part as the alternative foods for arthropod predators. This research was aimed to know the diversity and abundance of Collembola top soil on land area of Cruciferae in agrotourism and in the edge of the forest in Serang, Purbalingga, Central Java. The sampling was done using pitfall trap. The results showed that the abundance of Collembola on land area of Cruciferae in the edge of the forest is higher than on land area of Cruciferae in agrotourism, but the diversity of Collembola in agrotorism was not different from that of in the edge of the forest. Hypogastruridae was the family with the highest abundance on land area of Cruciferae in the edge of the forest, while Entomobryidae was the family with the highest abundance on land area of Cruciferae in agrotourism